Peran Redaktur Anonim dalam Teologi Kitab Obaja - Fiah, Yusri Lusinda M. (Sekolah Tinggi Teologi Sumatera Utara, 2023)
An observation of the work of the prophets is not only aimed at their words but at the assumption of secondary editorial additions to the texts. This approach is also supported by indications of the division of texts in this book. In general, the division based on the theme of the text's preaching, namely Obadiah 1:1-15 and 16-21, still seems to overlap in verse 15. This contradicts the opinion that the material of the book comes from Obadiah, supported by the argument that there is inconsistency with the news of the condemnation of the prophet's oration. In addition, this kitab is still filled with textual problems. The determination of the relationship between the two corridors in the division of textbook is a delicate aspect to establish. This paper displays the authorship and history of the conciliation of the book of Obadiah, as well as its theological applicability to the people moment for several purposes. The first is to trace the authorship of the book of Obaja and the process of assuaging the book to gain theological communication of the book for the people moment. This research will be conducted using logical constructions and interpretation exploration of the texts as part of qualitative research. Analysis of aspects of interpretation is carried out through critical studies centered on historical methods of redaction. AbstrakPerhatian karya para nabi yang tidak hanya ditujukan pada kata-kata mereka tetapi pada asumsi adanya tambahan-tambahan editorial sekunder terhadap teks-teks. Pendekatan ini didukung pula dengan adanya indikasi pembagian teks-teks pada kitab ini. Secara umum pembagian berdasarkan tema pemberitaan teks yaitu Obaja 1:1-15 dan 16-21 masih terlihat tumpang tindih pada ayat 15. Pendapat ini bertentangan dengan pendapat bahwa materi-materi kitab berasal dari Obaja, didukung oleh argumen yang menyatakan adanya kekonsistenan dengan berita penghukuman dari orasi nabi. Isi materi kitab ini masih dipenuhi dengan persoalan-persoalan tekstual. Penentuan hubungan antara kedua bagian dalam pembagian teks merupakan aspek yang sulit untuk dijalin. Tulisan ini menampilkan kepengarangan dan sejarah peredaksian Kitab Obaja, serta relevansi teologisnya bagi umat sekarang ini. Penelitian yang dilakukan penulis sebagai bagian dari penelitian kualitatif. Sementara analisis aspek-aspek penafsiran dilakukan melalui studi kritis dengan berpusat pada metode sejarah peredaksian.